On the occurrence of males and production of ephippial eggs in populations of Daphniopsis studeri (Cladocera) in lakes of the Vestfold and Larsemann Hills, East Antarctica - Gibson, JAE; Dartnall, HJG; Swadling, KM (Polar Biology, 1998)
Populations of the cladoceran Daphniopsis studeri Ruhe in freshwater and brackish lakes of eastern Antarctica have been thought to consist solely of females that reproduce parthenogenetically by the production of ameiotic subitaneous eggs. This note reports the presence of male D. studeri and the production of ephippial (sexual) eggs in a number of lakes of the Vestfold and Larsemann Hills, which indicate the possibility of sexual reproduction within these populations.